Binding Promises : the Late 20th-Century Reformation of Contract Law. - Slawson, W. David (Princeton University Press, 2001)
During its classical period, American contract law had three prominent characteristics: nearly unlimited freedom to choose the contents of a contract, a clear separation from the law of tort (the law of civil wrongs), and the power to make contracts without regard to the other party's ability to understand them. Combining incisive historical analysis with a keen sense of judicial politics, W. David Slawson shows how judges brought the classical period to an end about 1960 with a period of reform that continues to this day. American contract law no longer possesses any of the prominent character.